Unilateral Annulment of Marriage in Ancient Rome - Rašljanin, Imran (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The subject matter of this paper is unilateral annulment of marriage from the perspective of Roman law. In the Roman legal system, this institute was known as repudium. Repudiation was present both in matrimonium cum manu and in matrimonium sine manu. In matrimonium cum manu, repudiation was allowed only to men; in matrimonium sine manu, it was allowed to women as well. In this paper, the author examines the form, the requirements and repercussions of repudium in Roman law. The paper also considers the role of the paterfamilias, who had enormous power in the first half of the Roman Republic. Marriage could not take place without the consent of the paterfamilias; thus, it would be null and void ab initio in compliance with the rule quad nullum est nullum producit effectum. The liberalization of marital relations gradually contributed to reducing the role of the paterfamilias. Ultimately, repudiation resulted in a huge number of divorces. Such practices were perceived as a social problem by a number of Roman emperors, who tried to counteract the negative phenomenon by enacting relevant legislation.
Keywords: repudium; matrimonium cum manu; matrimonium sine manu; unilateral annulment of marriage